Achieving Large Second Harmonic Generation Effects via Optimal Planar Alignment of Triangular Units - Li, Xin‐Yu; Wei, Qi; Hu, Chun‐Li; Pan, Jie; Li, Bing‐Xuan; Xue, Zhen‐Zhen; Li, Xiao‐Yu; Li, Jin‐Hua; Mao, Jiang‐Gao; Wang, Guo‐Ming (Advanced functional materials, 2023)
Trigonal planar units with large polarizability anisotropy and high physicochemical stability are ideal structural units for exploring nonlinear optical (NLO) materials. Integrating the merits of two types of triangular‐like moieties, a family of second‐order NLO‐active hybrid halides, MATX (X = Cl (1), Br (2), and I (3)), are achieved. MATX crystallizes in a nonpolar space group of P6¯$P\overline 6 $2c but exhibits the optimal spatial arrangement and superior NLO performance. The low coordination planar trigonal AgX3 units enable segregation in layers of the three‐winged propeller‐like Me3TPA units. All of the layers are packed in a perfect parallel fashion, making the functional materials exhibit superior NLO performances, including the phase matchable behavior with strong SHG responses (6.2/1, 6.5/2, and 7.6/3 times that of potassium dihydrogen phosphate), large birefringence (0.232/1, 0.252/2 and 0.260/3 at 1064 nm), high laser damage threshold, wide transparent window, and easiness of crystal growth. The first‐principles calculations reveal that the coexistence of strong linear and nonlinear optical properties are ascribed to the synergistic effect of the trigonal moieties. This study points out a useful path for the rational design of excellent NLO materials. [Me3TPA][AgX3]X (X = Cl, Br or I) exhibits optimal planar alignment of two types of triangular‐like units and superior NLO performances, including the phase matchable behavior with strong second‐harmonic generation response, large birefringence, high LDT, wide band gap, and easiness of crystal growth.